(untitled) - Bigelow, Stephen J. (Boston, 2001)
Throughout its history, Understanding Telephone Electronics has been, by far, one of the most popular books on telecommunication electronics in the trade, electronic distribution, and educational markets because of its very simple, direct approach to the technology. In keeping with the distinguished tradition of its predecessors, Understanding Telephone Electronics, Fourth Edition covers conventional telephone fundamentals, including both analog and modern digital communication techniques, and provides basic information on the functions of each telephone system component, how electronic circuits generate dial tones, and how the latest digital transmission techniques work.Throughout its history, Understanding Telephone Electronics has been, by far, one of the most popular books on telecommunication electronics in the trade, electronic distribution, and educational markets because of its very simple, direct approach to the technology. In keeping with the distinguished tradition of its predecessors, Understanding Telephone Electronics, Fourth Edition covers conventional telephone fundamentals, including both analog and modern digital communication techniques, and provides basic information on the functions of each telephone system component, how electronic circuits generate dial tones, and how the latest digital transmission techniques work.
Keywords: Telephone,Điện thoại